An Inconvenient Expertise: French Colonial Sailors and Technological Knowledge in the Union Française. Issue 1 (1st March 2019) - Nasiali, Minayo
Abstract : In the 1950s, French shipping companies began to replace their old fleet of steamships with new diesel ships. They also began to lay off sailors from French Africa, claiming that the changing technology rendered their labor obsolete. The industry asserted that African sailors did not have the aptitude to do other, more skilled jobs aboard diesel vessels. But unemployed colonial sailors argued differently, claiming that they were both able and skilled. This article explores how unemployed sailors from French Africa cast themselves as experts, capable of producing technological knowledge about shipping. In so doing, they shaped racialized and gendered notions about labor and skill within the French empire. The arguments they made were inconvenient, I argue, because colonial sailors called into question hegemonic ideas about who could be modern and who had the right to participate in discourse about expertise.